Flinovia : flow induced noise and vibration issues and aspects : a focus on measurement, modeling, simulation and reproduction of the flow excitation and flow induced response /: flow induced noise and vibration issues and aspects : a focus on measurement, modeling, simulation and reproduction of the flow excitation and flow induced response. ([2015]) - Unknown
No abstract available